Oral HPV-associated dysplasia: is koilocytic dysplasia a separate entity? - Anaya-Saavedra, Gabriela; Vázquez-Garduño, Marcela (Frontiers in Oral Health, 2024)
Oral epithelial dysplasia associated with high-risk HPV infection has received different names since its initial description, such as oral Bowenoid lesions, HPV-associated intraepithelial neoplasia, and oral koilocytic dysplasia. Some features, identified in more or less quantity in some of the descriptions, like apoptotic keratinocytes, karyorrhexis, and mitosoid figures, are intricately connected to viral transcriptional status and, consequently, viral load. Since the variety in terminology has introduced diagnostic confusion within medical and research communities, establishing a uniform and standardized approach to diagnosing HPV-oral epithelial dysplasia is crucial for accurate and early diagnoses and holds significant implications for patient outcomes, particularly in high-risk individuals.